The relationship between the board characteristics and earnings management: Empirical evidence of Chinese Listed Companies - Yang, Xinyi (2020)
The widespread of earnings management leads that the reliability of disclosed financial information is in question. Earnings management stems from the imperfect corporate governance structure. Managers use the defects in corporate governance, intervening in the presentation of financial reports. Due to the fraud and financial scandals, related information users would have difficulty in measuring the corporate value effectively. Also, resource allocation in the capital market would be influenced. Therefore, how to control the level of earnings management has aroused great attention in the world. As the core of corporate governance structure, the board plays a vital role in guaranteeing the accuracy of the firm’s financial reports, which finally influences the degree of earnings management.